Case of erythema nodosum associated with granulomatous mastitis probably due to Corynebacterium infection. Issue 9 (September 2014) - Hida, Tetsuya; Minami, Mitsuyoshi; Kawaguchi, Hidetoshi; Oshiro, Yumi; Kubo, Yoshiaki
Abstract Granulomatous mastitis (GM) is a rare chronic inflammatory breast disease that can be mistaken for a variety of inflammatory and neoplastic disorders of the breast. Erythema nodosum (EN) is a common panniculitis, and is often associated with a variety of diseases, yet coexistence of EN and GM is very rare. In this paper, we present a young Japanese woman with EN associated with GM probably due to Corynebacterium infection. Both lesions of EN and GM were successfully treated with oral minocycline and surgical drainage. To the best of our knowledge, this is the first case of EN associated with GM due to Corynebacterium infection in the English‐language published work.